2018
DOI: 10.1111/aogs.13392
|View full text |Cite
|
Sign up to set email alerts
|

Increased cardiovascular disease risk in women with a history of recurrent miscarriage

Abstract: IntroductionCardiovascular disease is the leading cause of death in women. Observational studies suggest that women with a history of recurrent miscarriage have an increased risk of cardiovascular disease.Material and methodsWomen who visited the recurrent miscarriage clinic at Leiden University Medical Center between 2000 and 2010 and who had their third consecutive miscarriage before the age of 31 years, were invited to participate in this follow‐up study (between 2012 and 2014). The reference group consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…Pre-eclampsia and other obstetric complications have been included in the American Heart Association guidelines as cardiovascular risk factors for women, but miscarriage was omitted despite the fact that some of these complications share common pathological origins with miscarriage [11]. Furthermore, research through large population studies and meta-analyses has confirmed the strong association of miscarriage with cardiovascular outcomes, providing another reason for scientists to consider miscarriage in the assessment of future cardiovascular risk [12][13][14]. However, the link between miscarriage and the subsequent development of cardiovascular disease are not well argued or documented.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-eclampsia and other obstetric complications have been included in the American Heart Association guidelines as cardiovascular risk factors for women, but miscarriage was omitted despite the fact that some of these complications share common pathological origins with miscarriage [11]. Furthermore, research through large population studies and meta-analyses has confirmed the strong association of miscarriage with cardiovascular outcomes, providing another reason for scientists to consider miscarriage in the assessment of future cardiovascular risk [12][13][14]. However, the link between miscarriage and the subsequent development of cardiovascular disease are not well argued or documented.…”
Section: Introductionmentioning
confidence: 99%
“…Various therapeutic strategies such as immunologic intervention with allogenic lymphocyte [ 9 ] and immunoglobulin [ 10 ], anticoagulant therapy using aspirin [ 11 ] or low-molecular weight heparin [ 12 ], hormonal supplementation with progesterone or dydrogesterone [ 13 ], and microelements supplementation, such as vitamin E, vitamin D [ 14 ], and folic acid [ 15 ], have been used to improve pregnancy outcomes among these women, but no effective treatment has been identified. To date, there is no widely accepted therapeutic approaches for URSA [ 16 ], bringing seriously physical and mental impacts to both the affected female population and their families [ 17 19 ]. Therefore, it is essential to investigate effective treatments to reduce pregnancy losses and maintain successful pregnancy preservation in patients with URSA.…”
Section: Introductionmentioning
confidence: 99%
“…Жінки, що перенесли втрати вагітності, зазнають стресу, через що порушуються функції цілого організму [7,9,15,16]. Вони також мають підвищений ризик кардіоваскулярних захворювань [14], які, як відомо, асоціюються із короткими теломерами [4,6]. Отже, довжина теломер є суттєво меншою у жінок із ранніми репродуктивними втратами.…”
Section: результати та обговоренняunclassified